METHODOLOGY FOR DEVELOPING WILL MAKING QUALITIES IN ATHLETES (Web of Teachers: Inderscience Research, 2025)
This article provides a scientific analysis of the methods for forming and developing volitional qualities in athletes, as well as the coach's methodological activities and educational psychological approaches in this process. Additionally, effective methods and exercises aimed at increasing athletes' patience, determination, and self-control abilities are highlighted.